Solid-state electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202611479179.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]硫化物电解质的材料化学稳定性差,对水氧极为敏感,极易与空气中的水汽及氧反应释放硫化氢,显著增加了生产与使用风险
[0021]本发明提供一种固态电解质及其制备方法和应用,至少具有如下有益效果:本发明的固态电解质通过对硫化物电解质内核进行晶格掺杂与双层包覆的协同设计,显著提升了其综合性能。具体而言,晶格掺杂通过掺杂基团(如氮掺杂基团和/或含氟掺杂基团)进入晶格调控键合环境,拓宽锂离子迁移通道并降低跃迁能垒,同时增强基体骨架键能,提升内核本征抗水氧能力;第一包覆层(内层)致密化学惰性锂离子导体包覆层通过物理隔离阻隔水氧渗透,并钝化内核表面活性位点,避免高阻抗副产物生成,从而保障界面化学稳定性;第二包覆层(外层)具有玻璃态柔性的锂离子导体包覆层,在热压过程中发生软化流动,将固-固接触由点接触转变为面接触,降低界面阻抗,利于缓冲电极体积变化应力,维持界面结构完整,双层包覆形成梯度功能分区:内层侧重化学环境防护,外层侧重离子传导与界面适配,两者协同克服了单一包覆层难以兼顾多重性能的难题,本发明的固态电解质兼具高离子电导率、优异空气稳定性和界面兼容性,可适配多种正负极材料,显著提升全固态电池的循环寿命与安全性。
Smart Images

Figure SMS_2 
Figure SMS_5 
Figure SMS_6
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state electrolyte batteries, specifically to a solid-state electrolyte, its preparation method, and its application. Background Technology
[0002] Sulfide solid electrolytes are considered one of the most promising electrolyte materials for all-solid-state batteries due to their high room-temperature ionic conductivity, good machinability, and contact compatibility with lithium metal anodes, and have become a core research direction for next-generation solid-state battery electrolytes. Currently, mainstream sulfide electrolytes such as Li... 10 GeP2S 12 (LGPS), Li7P3S 11 Although Li6PS5X (X=Cl, Br, I) and other compounds have shown excellent ion conduction properties, they still have many shortcomings.
[0003] Sulfide electrolytes exhibit poor chemical stability and are extremely sensitive to water and oxygen. They readily react with water vapor and oxygen in the air to release hydrogen sulfide, significantly increasing the risks associated with production and use. Furthermore, sulfide electrolytes are prone to interfacial side reactions when in contact with lithium metal anodes, forming a high-resistivity interfacial layer and failing to effectively suppress lithium dendrite growth, severely limiting their practical applications.
[0004] To address the aforementioned issues, existing technologies often employ single doping or single coating to modify materials. However, single doping only affects the bulk phase; doping methods that increase ionic conductivity weaken lattice bond energy and reduce chemical stability, while doping that enhances stability increases the ion migration barrier. Single coating faces a trade-off between protective effect and ion transport efficiency: a dense coating layer increases interfacial impedance, while a thinner coating layer provides insufficient protection and is prone to peeling. Furthermore, materials treated with conventional mixed coating processes are prone to phase separation during heat treatment, making it difficult to form a uniform, continuous, and low-impedance composite protective layer. In some cases, the coating layer may even crack due to a mismatch in thermal expansion coefficients. Therefore, modified materials still struggle to simultaneously achieve high ionic conductivity and good chemical stability.
[0005] Therefore, developing a sulfide electrolyte product that combines high ionic conductivity and excellent chemical stability with the ability to effectively reduce side reactions and lower interfacial impedance is of great significance for promoting the commercialization of all-solid-state batteries. Summary of the Invention
[0006] This invention provides a solid electrolyte, its preparation method, and its application. The solid electrolyte is suitable for all-solid-state batteries, and has both high ionic conductivity and excellent chemical stability, which can effectively reduce side reactions and lower interfacial impedance.
[0007] In a first aspect, embodiments of the present invention provide a solid electrolyte comprising a core, a first coating layer located on at least a portion of the surface of the core, and a second coating layer located on at least a portion of the surface of the first coating layer opposite to the core; wherein the core comprises a sulfide solid electrolyte, the sulfide solid electrolyte comprising dopant groups doped in a crystal lattice, the dopant groups comprising nitrogen dopant groups and / or fluorine dopant groups; the first coating layer comprises a chemically inert lithium-ion conductor; and the second coating layer comprises a glassy flexible lithium-ion conductor.
[0008] Optionally, the matrix of the sulfide solid electrolyte includes Li. 5.5 PS 4.5 Cl 1.5-x Br x , 0≤x≤1.5.
[0009] Optionally, the chemically inert lithium-ion conductor includes at least one of lithium phosphate, lithium carbonate, and lithium sulfate; and / or, the glassy flexible lithium-ion conductor includes at least one of lithium borate, lithium metaborate, and lithium tetraborate.
[0010] Optionally, the molar ratio of the chemically inert lithium-ion conductor to the glassy flexible lithium-ion conductor is (2~4):(6~8); and / or, the thickness of the first coating layer is 5nm~15nm; and / or, the thickness of the second coating layer is 5nm~25nm; and / or, the ratio of the mass of the core to the sum of the masses of the first coating layer and the second coating layer is 1:(0.01~0.05).
[0011] In a second aspect, embodiments of the present invention provide a method for preparing a solid electrolyte, comprising the following steps: (1) sequentially grinding and annealing a raw material system including a sulfide solid electrolyte precursor and a dopant source to obtain a sulfide solid electrolyte precursor; wherein the dopant source includes a nitrogen-doped group and / or a fluorine-doped group; (2) first mixing the sulfide solid electrolyte precursor with a first solution containing the chemically inert lithium-ion conductor to obtain a first mixture; then sequentially subjecting the first mixture to a first drying treatment and a second annealing treatment to obtain an intermediate; (3) second mixing the intermediate with a second solution containing the glassy flexible lithium-ion conductor to obtain a second mixture; then sequentially subjecting the second mixture to a second drying treatment and a third annealing treatment to obtain the solid electrolyte.
[0012] Optionally, the doping source includes at least one of lithium nitride and lithium fluoride; and / or, the sulfide solid electrolyte precursor raw material includes at least one of Li2S, P2S5, LiCl, and LiBr; and / or, the molar ratio of the doping source to the matrix of the sulfide solid electrolyte is (0.005~0.04):1.
[0013] Optionally, the grinding speed is 300 rpm to 500 rpm; and / or the grinding time is 8 h to 16 h; and / or the temperature of the first annealing is 260 °C to 320 °C; and / or the time of the first annealing is 5 h to 10 h.
[0014] Optionally, the first solution further includes a first organic solvent, which includes at least one of anhydrous ethanol, anhydrous acetonitrile, and dimethyl carbonate; and / or, the concentration of the chemically inert lithium-ion conductor in the first solution is 0.015 mol / L to 0.036 mol / L; and / or, the second solution further includes a second organic solvent, which includes at least one of anhydrous ethanol, anhydrous acetonitrile, and dimethyl carbonate; and / or, the concentration of the glassy flexible lithium-ion conductor in the second solution is 0.035 mol / L to 0.084 mol / L.
[0015] Optionally, the solid content of the first mixture is 8%~15%; and / or, the process of first mixing the sulfide solid electrolyte precursor and the first solution containing the chemically inert lithium-ion conductor to obtain the first mixture includes: mixing the sulfide solid electrolyte precursor and the first solution containing the chemically inert lithium-ion conductor, and then sequentially performing first stirring, first ultrasonic treatment, and second stirring to obtain the first mixture; wherein, the first stirring speed is 300rpm~500rpm and the time is 2h~5h, and ... The ultrasonic treatment has a power of 100W~200W and a time of 10min~20min; the second stirring speed is 300rpm~500rpm and the time is 0.5h~1h; and / or, the first drying treatment includes a first stage and a second stage, the temperature of the first stage is 40℃~100℃ and the time is 1h~3h, the temperature of the second stage is 100℃~120℃ and the time is 3h~5h; and / or, the temperature of the second annealing treatment is 250℃~300℃; and / or, the time of the second annealing treatment is 2h~4h.
[0016] Optionally, the process of mixing the intermediate with the second solution containing the glassy flexible lithium-ion conductor to obtain the second mixture includes: mixing the intermediate with the second solution containing the glassy flexible lithium-ion conductor, followed by third stirring, second ultrasonic treatment, and fourth stirring to obtain the second mixture; the third stirring speed is 300 rpm to 500 rpm and the time is 2 h to 5 h; the second ultrasonic treatment power is 100 W to 200 W and the time is 10 min to 20 min; the fourth stirring speed is 300 rpm to 500 rpm and the time is 0.5 h to 1 h; and / or, the second drying treatment includes a third stage and a fourth stage, the temperature of the third stage is 40 °C to 100 °C and the time is 1 h to 3 h; the temperature of the fourth stage is 100 °C to 120 °C and the time is 3 h to 5 h; and / or, the temperature of the third annealing treatment is 250 °C to 300 °C; and / or, the time of the third annealing treatment is 2 h to 4 h.
[0017] Thirdly, embodiments of the present invention provide a solid electrolyte membrane, comprising the above-described solid electrolyte or the solid electrolyte prepared according to the above-described solid electrolyte preparation method.
[0018] Fourthly, embodiments of the present invention provide an electrode, the electrode comprising a current collector and an active coating present on at least one side of the current collector, wherein the active coating comprises the solid electrolyte described above or the solid electrolyte prepared by the method described above.
[0019] Optionally, the electrode is a negative electrode or a positive electrode.
[0020] Fifthly, embodiments of the present invention provide an all-solid-state battery, including the above-described solid electrolyte membrane or the above-described electrode sheet.
[0021] This invention provides a solid electrolyte, its preparation method, and its applications, which have at least the following beneficial effects: The solid electrolyte of this invention significantly improves its overall performance through the synergistic design of lattice doping and double-layer coating on the sulfide electrolyte core. Specifically, lattice doping introduces dopant groups (such as nitrogen-doped groups and / or fluorine-containing dopant groups) into the lattice-regulated bonding environment, broadens the lithium-ion migration channels and lowers the transition energy barrier, while enhancing the matrix framework bond energy and improving the intrinsic water and oxygen resistance of the core; the first coating layer (inner layer) is a dense, chemically inert lithium-ion conductor coating layer that physically isolates and blocks water and oxygen penetration and passivates the active sites on the core surface, avoiding the formation of high-resistance byproducts, thereby ensuring the chemical stability of the interface; the second coating layer (outer layer) has a glassy, flexible lithium-ion conductor coating layer, in During hot pressing, softening flow occurs, transforming the solid-solid contact from point contact to surface contact, reducing interfacial impedance, facilitating the buffering of electrode volume change stress, maintaining the integrity of the interfacial structure, and forming a gradient functional zone with double-layer coating: the inner layer focuses on chemical environment protection, while the outer layer focuses on ion conduction and interface compatibility. The two work together to overcome the problem that a single coating layer cannot take into account multiple performances. The solid electrolyte of this invention has high ionic conductivity, excellent air stability, and interface compatibility, and can be adapted to a variety of positive and negative electrode materials, significantly improving the cycle life and safety of all-solid-state batteries. Detailed Implementation
[0022] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] In a first aspect, embodiments of the present invention provide a solid electrolyte comprising a core, a first coating layer located on at least a portion of the surface of the core, and a second coating layer located on at least a portion of the surface of the first coating layer opposite to the core; wherein the core comprises a sulfide solid electrolyte, the sulfide solid electrolyte comprising dopant groups doped in a crystal lattice, the dopant groups comprising nitrogen dopant groups and / or fluorine dopant groups; the first coating layer comprises a chemically inert lithium-ion conductor; and the second coating layer comprises a glassy flexible lithium-ion conductor.
[0024] According to research and analysis, the solid electrolyte of this invention significantly improves its overall performance through the synergistic design of lattice doping and double-layer coating on the sulfide electrolyte core. Specifically, lattice doping introduces dopant groups (such as nitrogen-doped groups and / or fluorine-containing dopant groups) into the lattice to regulate the bonding environment, broadening lithium-ion migration channels and reducing transition energy barriers, while simultaneously enhancing the matrix framework bond energy and improving the core's intrinsic resistance to water and oxygen; the first coating layer (inner layer) is a dense, chemically inert lithium-ion conductor coating layer that physically isolates and blocks water and oxygen penetration, and passivates the active sites on the core surface, avoiding the formation of high-resistance byproducts, thereby ensuring interfacial chemical stability; the second coating layer (outer layer) is a glassy, flexible lithium-ion conductor coating layer, in During hot pressing, softening flow occurs, transforming the solid-solid contact from point contact to surface contact, reducing interfacial impedance, facilitating the buffering of electrode volume change stress, maintaining the integrity of the interfacial structure, and forming a gradient functional zone with double-layer coating: the inner layer focuses on chemical environment protection, while the outer layer focuses on ion conduction and interface compatibility. The two work together to overcome the problem that a single coating layer cannot take into account multiple performances. The solid electrolyte of this invention has high ionic conductivity, excellent air stability, and interface compatibility, and can be adapted to a variety of positive and negative electrode materials, significantly improving the cycle life and safety of all-solid-state batteries.
[0025] The matrix of the sulfide solid electrolyte may include a sulfide solid electrolyte of the sulfide type (Li6PS5X, where X is at least one of Cl and Br). Further, the matrix of the sulfide solid electrolyte may include Li... 5.5 PS 4.5 Cl 1.5-x Br x (LPSCB), 0≤x≤1.5, where x can take the values of 0, 0.5, 0.75, 1, 1.5 or any combination of two of these.
[0026] The matrix of a sulfide solid electrolyte refers to the main lattice framework material that constitutes the sulfide solid electrolyte. Its chemical composition can be adjusted as needed. By introducing doping elements (such as nitrogen and fluorine) into the lattice, the crystal field and bonding environment can be controlled to optimize the ion conduction performance and chemical stability of the solid electrolyte.
[0027] By adjusting the x value, a continuously adjustable compositional window can be formed in the matrix between chlorine doping and bromine doping. For example, when x is 0.75, Li can be obtained. 5.5 PS 4.5 Cl 0.75 Br 0.75 The balanced co-doped structure is obtained, and when x takes the values of 0, 0.5, 1 or 1.5, it corresponds to different degrees of Br substitution ratio, thereby regulating the local environment of the matrix lattice, ion migration channels and particle densification behavior.
[0028] Specifically, the sulfide solid electrolyte includes doped groups doped in the crystal lattice, including nitrogen-doped groups and / or fluorine-doped groups.
[0029] The doping source can provide nitrogen-doped groups and / or fluorine-containing doping groups. Using these doping groups can effectively broaden the lithium-ion transport channels and improve the bulk ion conduction efficiency. On the other hand, it can reduce the surface affinity of the matrix to moisture, inhibit moisture absorption and deterioration, and enhance the electrolyte's ability to mechanically block and chemically passivate lithium dendrites, thereby achieving synergistic improvement in both conductivity and environmental adaptability.
[0030] Nitrogen-doped groups can alter the local electronic environment near the PS framework and modulate the lithium-ion migration barrier; fluorine-doped groups can utilize their strong chemical bonding characteristics to reduce the surface reaction tendency of the material when it comes into contact with water, oxygen, or highly active electrodes, thereby coordinating bulk conductivity and chemical stability within the same core.
[0031] The first coating layer includes a chemically inert lithium-ion conductor.
[0032] In this application, "chemical inertness" means that when lithium-ion conductor materials come into contact with the ambient atmosphere (moisture, oxygen) and adjacent layers (such as lithium metal anodes), under the conditions of solid electrolyte preparation, storage and service, they do not produce irreversible chemical or electrochemical side reactions and do not form a high-resistivity interface layer, while possessing effective lithium-ion conduction capabilities.
[0033] Furthermore, chemically inert lithium-ion conductors may include at least one of lithium phosphate (Li3PO4), lithium carbonate (Li2CO3), and lithium sulfate (Li2SO4).
[0034] Chemically inert lithium-ion conductors meet the above criteria, enabling solid electrolytes to have better chemical stability and lithium-ion mobility. They can form a dense insulating layer on the outer surface of sulfide solid electrolyte particles, reducing water and oxygen erosion and suppressing side reactions with electrode materials.
[0035] Furthermore, the thickness of the first coating layer can be 5nm to 15nm, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15nm or any combination thereof.
[0036] The thickness of the first coating layer meets the above-mentioned range, which can form a continuous and dense chemical isolation layer on the core surface to suppress water and oxygen intrusion and side reactions with the electrode, without significantly increasing the lithium ion crossing distance and transmission impedance due to excessive coating thickness.
[0037] The second coating layer includes a glassy, flexible lithium-ion conductor.
[0038] In this application, "glassy flexibility" refers to the ability of a glassy flexible lithium-ion conductor to undergo a glass transition within the target heat treatment temperature range, forming an amorphous or glass-ceramic composite interface phase. In this state, the glassy flexible material exhibits viscous flow capability in the particle contact area, filling the micron-sized voids between particles and at the interface, and forming continuous lithium-ion transport channels after solidification, thus possessing the dual functions of interface adaptation and ion conduction.
[0039] Specifically, glassy flexibility can be characterized by differential scanning calorimetry (DSC): Take the coated sample powder and heat it from room temperature to 600℃ at a heating rate of 10℃ / min under an inert atmosphere. Record the DSC curve of heat flow as a function of temperature. If a step-like transition in the endothermic direction occurs in the temperature range of 300℃ to 500℃, it indicates that the material has glassy flexibility.
[0040] A glassy flexible lithium-ion conductor may include at least one of lithium borate (Li3BO3), lithium metaborate (LiBO2), and lithium tetraborate (Li2B4O7).
[0041] Lithium-ion conductors with glassy flexibility meet the above criteria and can form a glassy phase after appropriate annealing. Their amorphous structure is conducive to building continuous lithium-ion migration channels, while reducing the contact resistance between particles and electrodes. Furthermore, their chemical inertness can effectively suppress the occurrence of interfacial side reactions.
[0042] The first and second coating layers work together to simultaneously improve the chemical stability, interfacial compatibility, and lithium-ion cross-interface migration efficiency of the solid electrolyte, thereby reducing internal resistance, slowing down degradation, and extending the cycle life of the all-solid-state battery.
[0043] Furthermore, the thickness of the second coating layer can be 5nm to 25nm, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25nm or any combination thereof, and the thickness of the total coating layer (the first coating layer and the second coating layer) can be 10nm to 40nm.
[0044] The thickness of the second coating layer meets the above range, which can avoid discontinuous coverage and coating layer peeling due to being too thin, or increased ion diffusion path due to being too thick. This can further achieve a balance between interface adhesion and rapid ion migration across the interface, and improve the contact stability between the electrode and the solid electrolyte.
[0045] Furthermore, the molar ratio of the chemically inert lithium-ion conductor to the glassy flexible lithium-ion conductor can be (2~4):(6~8), for example, 2:8, 3:7, 4:6 or any combination thereof.
[0046] When the molar ratio of chemically inert lithium-ion conductors to glassy flexible lithium-ion conductors meets the above-mentioned range, the chemically inert component can preferentially provide a stable chemical barrier, while the glassy flexible lithium-ion conductors improve interfacial conduction through higher ion migration compliance, thereby balancing barrier properties and conductivity, and enabling the first and second coating layers to form a more coordinated transport channel.
[0047] In some embodiments, the ratio of the mass of the kernel to the sum of the masses of the first and second overlays can be 1:(0.01 to 0.05), for example, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05 or any combination thereof.
[0048] The ratio of the mass of the core to the sum of the masses of the first and second coating layers satisfies the above range, which ensures that the solid electrolyte as a whole still undertakes the main conduction function with the high conductivity sulfide core. At the same time, the double coating provides chemical stability and interface compatibility, effectively improving the reliability of the solid electrolyte in air environment and in contact with lithium metal without significantly sacrificing the intrinsic ionic conductivity of the matrix.
[0049] The solid electrolyte prepared by this invention has an ionic conductivity of not less than 1.0 × 10⁻⁶ at room temperature (25°C). -3 S / cm, after exposure to ambient air (relative humidity 20%~30%) for 24 hours, its ionic conductivity retention rate is not less than 80%.
[0050] In a second aspect, embodiments of the present invention provide a method for preparing the above-mentioned solid electrolyte, comprising the following steps: (1) sequentially grinding and first annealing a raw material system including a sulfide solid electrolyte precursor and a dopant source to obtain a sulfide solid electrolyte precursor; wherein the dopant source includes a nitrogen dopant group and / or a fluorine dopant group; (2) first mixing the sulfide solid electrolyte precursor and a first solution containing a chemically inert lithium-ion conductor to obtain a first mixture; then sequentially subjecting the first mixture to a first drying treatment and a second annealing treatment to obtain an intermediate; (3) second mixing the intermediate and a second solution containing a glassy flexible lithium-ion conductor to obtain a second mixture; then sequentially subjecting the second mixture to a second drying treatment and a third annealing treatment to obtain a solid electrolyte.
[0051] This invention first modulates the lattice of a sulfide solid electrolyte matrix through lattice doping to optimize lithium-ion migration channels and enhance bulk ion conductivity. Then, a first coating layer (inner layer) and a second coating layer (outer layer) are sequentially constructed using a liquid-phase-thermal treatment (annealing) process. The first coating layer effectively blocks solvent and moisture erosion, preventing matrix degradation during preparation and storage. The second coating layer, after annealing, forms a glassy interface phase, which not only reduces the interfacial impedance between the electrolyte and the electrode but also suppresses interfacial side reactions. The resulting sulfide solid electrolyte exhibits both high ionic conductivity and excellent chemical stability, while simultaneously reducing energy consumption during the preparation process.
[0052] The preparation of solid electrolytes can be carried out entirely in an inert atmosphere, isolating water and oxygen (the content of both water and oxygen is ≤0.01ppm).
[0053] (1) The raw material system including sulfide solid electrolyte precursor raw material and dopant source is subjected to grinding and first annealing treatment in sequence to obtain sulfide solid electrolyte precursor.
[0054] The doping source can provide nitrogen-doped groups and / or fluorine-doped groups, and further, the doping source may include at least one of lithium nitride and lithium fluoride.
[0055] The doping source meets the above criteria and can release nitrogen-doped groups and / or fluorine-containing doped groups during the grinding and first annealing process, which can enter the lattice sites or grain boundary regions of the sulfide solid electrolyte, thereby regulating the local coordination environment and optimizing the ion conduction performance and chemical stability of the solid electrolyte.
[0056] In one possible embodiment, the raw materials and doping sources of the sulfide solid electrolyte precursor can be selected according to the composition and ratio of the target sulfide solid electrolyte precursor.
[0057] The grinding process can be carried out under an inert atmosphere to ensure uniform contact between the sulfide solid electrolyte precursor raw material and the dopant source and reduce the reaction diffusion distance.
[0058] Furthermore, the precursor materials for sulfide solid electrolytes may include at least one of Li2S, P2S5, LiCl, and LiBr.
[0059] The aforementioned sulfide solid electrolyte precursor raw materials can provide sulfide framework and halogen components to form the required matrix composition.
[0060] The matrix can be obtained by configuring the raw materials of the sulfide solid electrolyte precursor according to the stoichiometric ratio. Specifically, the molar ratio of Li2S, P2S5, LiCl and LiBr can be 2:0.5:(1-x):x, 0≤x≤1.5. Specifically, the value of x can be 0, 0.5, 0.75, 1, 1.5 or any combination of two of them.
[0061] In some specific embodiments, the molar ratio of the dopant source to the matrix of the sulfide solid electrolyte can be (0.005~0.04):1, for example, 0.005:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1 or any combination thereof.
[0062] By controlling the molar ratio of the dopant source to the sulfide solid electrolyte precursor raw material within the above range, the doping amount can be kept within a range that is sufficient to improve the crystal structure without causing obvious secondary phase formation, thereby providing a stable sulfide solid electrolyte precursor for subsequent coating to form a uniform interface.
[0063] The grinding speed can be 300 rpm to 500 rpm, for example, 300, 400, 500 rpm or any combination thereof.
[0064] If the grinding speed meets the above range, the solid particles in the raw material system can obtain sufficient collision and shearing action, thereby promoting the uniform mixing of the raw material system and the dispersion of dopant sources.
[0065] The grinding time can be 8h to 16h, for example, 8, 9, 10, 11, 12, 13, 14, 15, 16h or any combination thereof.
[0066] The grinding time must be within the above range to allow nitrogen-doped groups and / or fluorine-doped groups to participate more fully in the formation process of the sulfide solid electrolyte precursor, avoiding uneven mixing or insufficient reaction due to insufficient time.
[0067] Specifically, the grinding process can be ball milling, which can use grinding balls and grinding jars, both made of zirconium oxide.
[0068] Furthermore, the grinding balls include small grinding balls (e.g., diameters of 1mm to 5mm, excluding 5mm, such as 1mm or 2mm) and large grinding balls (e.g., diameters of 5mm to 10mm, such as 5mm or 10mm). During grinding, the mass ratio of large grinding balls to small grinding balls can be 1:1, and the mass ratio of the grinding balls to the total mass of the raw material system, including the sulfide solid electrolyte precursor raw material and the dopant source, can be (15 to 30):1, such as 15:1, 20:1, 25:1, 30:1, or any combination thereof. This allows the particles of the raw material system to be rapidly refined during the grinding process, and to obtain a concentrated and controllable particle size distribution. This provides a uniform reaction substrate for the subsequent lattice diffusion of doped elements, while ensuring that the coating layer has consistent spreading conditions and thickness control on the surface of each particle.
[0069] After grinding, the particle size D of the raw material system V50 It can be 10μm to 20μm, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20μm or any combination thereof.
[0070] Particle size D of the raw material system V50 Meeting the above range is beneficial for increasing the contact area between raw materials during the doping process, promoting the uniformity of solid-phase reaction and lattice diffusion of dopant elements, reducing the formation of impurity phases, and ensuring the high ionic conductivity of the matrix.
[0071] In some embodiments, the temperature of the first annealing treatment can be 260°C to 320°C, for example, 260, 270, 280, 290, 300, 310, 320°C or any combination thereof. Specifically, the heating rate of the first annealing treatment can be 2°C / min.
[0072] The temperature of the first annealing treatment meets the above range, which can promote the solid-phase reaction of the ground raw material system and form a sulfide solid electrolyte precursor.
[0073] The first annealing process can take 5 to 10 hours, for example, 5, 6, 7, 8, 9, 10 hours or any combination thereof.
[0074] The time for the first annealing treatment must be within the above range to ensure that the heat treatment process is carried out sufficiently, so that the dopant component can stably enter the crystal lattice or be uniformly distributed in the precursor.
[0075] (2) The sulfide solid electrolyte precursor and the first solution containing a chemically inert lithium-ion conductor are first mixed to obtain a first mixture; then the first mixture is subjected to a first drying treatment and a second annealing treatment to obtain an intermediate.
[0076] For example, step (2) may specifically include: mixing a sulfide solid electrolyte precursor and a first solution containing a chemically inert lithium-ion conductor in a first mixing, and then performing a first stirring, a first ultrasonic treatment and a second stirring in sequence to obtain a first mixture; and then subjecting the first mixture to a first drying treatment and a second annealing treatment in sequence to obtain an intermediate.
[0077] The first solution may include a chemically inert lithium-ion conductor and a first organic solvent.
[0078] The first organic solvent may include at least one of anhydrous ethanol, anhydrous acetonitrile, and dimethyl carbonate, and further, the first organic solvent may include anhydrous ethanol.
[0079] The first organic solvent meets the above requirements and can provide a low-water-content environment and reduce the risk of hydrolysis of sulfide solid electrolyte precursors.
[0080] The concentration of the chemically inert lithium-ion conductor in the first solution can be from 0.015 mol / L to 0.036 mol / L, for example, 0.015, 0.02, 0.03, 0.036 mol / L or any combination thereof.
[0081] The concentration of the chemically inert lithium-ion conductor meets the above range, enabling it to form a uniform, continuous, and not too thick first coating layer when in contact with the sulfide solid electrolyte precursor, avoiding incomplete coverage due to too low a concentration or crystallization and agglomeration due to too high a concentration.
[0082] The initial stirring speed can be 300 rpm to 500 rpm, for example, 300, 400, 500 rpm or any combination thereof.
[0083] The first stirring speed meets the above range, which can form a uniform first mixture (initial suspension system) and promote uniform contact between sulfide solid electrolyte precursor particles and chemically inert lithium-ion conductors.
[0084] The first stirring time can be 2 hours to 5 hours, for example, 2, 3, 4, 5 hours or any combination thereof.
[0085] The first stirring time meets the above range, which can form a uniform first mixture (initial suspension system) and promote uniform contact between sulfide solid electrolyte precursor particles and chemically inert lithium-ion conductors.
[0086] The power of the first ultrasonic treatment can be 100W to 200W, for example, 100, 150, 200 or any combination thereof.
[0087] The power of the first ultrasonic treatment meets the above range and can break up soft aggregates by means of cavitation effect and enhance the penetration of the first solution into the surface of sulfide solid electrolyte precursor particles.
[0088] The duration of the first ultrasonic treatment can be 10 min to 20 min, for example, 10, 15, 20 min or any combination thereof.
[0089] The time for the first ultrasonic treatment meets the above range, which can break up soft agglomerates by means of cavitation effect and enhance the penetration of the first solution into the surface of sulfide solid electrolyte precursor particles.
[0090] Furthermore, the first ultrasonic treatment can be intermittent ultrasonic treatment, for example, ultrasonic time of 1 min to 3 min and interval time of 0.5 min to 1 min, to prevent the temperature of the slurry from rising due to continuous energy input during the ultrasonic process, which would affect the uniformity of the coating layer. At the same time, it can also promote the removal of dissolved gases in the slurry, and inhibit secondary agglomeration of particles to maintain the stability of the system.
[0091] The second stirring speed can be 300 rpm to 500 rpm, for example, 300, 400, 500 rpm or any combination thereof.
[0092] The second stirring speed meets the above range and can be used to stabilize the dispersion state of the first mixture and promote the uniform adsorption or deposition of chemically inert lithium-ion conductors on the particle surface.
[0093] The second stirring time can be 0.5h to 1h, for example, 0.5, 0.75, 1h or any combination thereof.
[0094] The second stirring time meets the above range and can be used to stabilize the dispersion state of the first mixture and promote the uniform adsorption or deposition of chemically inert lithium-ion conductors on the particle surface.
[0095] The first drying process may include a first stage and a second stage.
[0096] Specifically, the temperature of the first stage can be 40℃~100℃, for example, 40, 50, 60, 70, 80, 90, 100℃ or any combination thereof.
[0097] The temperature in the first stage meets the above range, which is sufficient to slowly remove most of the first organic solvent.
[0098] The duration of the first phase can be 1 hour to 3 hours, for example, 1, 2, 3 hours or any combination thereof.
[0099] The time frame of the first stage meets the above range, enabling the slow removal of most of the first organic solvent.
[0100] The temperature in the second stage can be 100℃~120℃, for example, 100, 110, 120℃ or any combination thereof.
[0101] The temperature in the second stage meets the above range, which can further remove the residual first organic solvent and obtain a calcinable intermediate solid.
[0102] The second phase can last from 3 to 5 hours, for example, 3, 4, 5 hours or any combination thereof.
[0103] The second stage time meets the above range, which can further remove the residual first organic solvent and obtain a calcinable intermediate solid.
[0104] The temperature for the second annealing treatment can be 250℃~300℃, for example, 250, 260, 270, 280, 290, 300℃ or any combination thereof. Specifically, the heating rate for the second annealing treatment can be 2℃ / min.
[0105] The temperature of the second annealing treatment meets the above range, which enables the chemically inert lithium-ion conductor in the first solution to form a stable intermediate binding state (intermediate) with the surface of the sulfide solid electrolyte precursor, and provides a uniform basis for the subsequent construction of the second coating layer.
[0106] The second annealing process can take 2 to 4 hours, for example, 2, 3, 4 hours or any combination thereof.
[0107] The second annealing time meets the above range, which enables the chemically inert lithium-ion conductor in the first solution to form a stable intermediate binding state (intermediate) with the surface of the sulfide solid electrolyte precursor, and provides a uniform basis for the subsequent construction of the second coating layer.
[0108] In some embodiments, the solid content of the first mixture can be 8% to 15%, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or any combination thereof.
[0109] Solid content refers to the mass percentage of the sulfide solid electrolyte precursor in the first mixture. When the solid content meets the above range, the sulfide solid electrolyte precursor and the first solution containing chemically inert lithium-ion conductors can maintain a rheological state suitable for dispersion and coating. If the solid content is too low, it will reduce the probability of effective collision and deposition. If the solid content is too high, it will cause the viscosity of the system to increase and agglomeration to intensify. Therefore, this range can take into account both the uniformity of subsequent mixing and the continuity of coating.
[0110] (3) The intermediate and the second solution containing a glassy flexible lithium-ion conductor are mixed for the second time to obtain a second mixture; then the second mixture is subjected to a second drying treatment and a third annealing treatment in sequence to obtain a solid electrolyte.
[0111] For example, step (3) may specifically include: mixing the intermediate and the second solution containing a glassy flexible lithium-ion conductor in a second mixing, and then performing a third stirring, a second ultrasonic treatment and a fourth stirring in sequence to obtain a second mixture; and then subjecting the second mixture to a second drying treatment and a third annealing treatment in sequence to obtain a solid electrolyte.
[0112] During the third annealing process, when the temperature rises to the glass transition temperature (T0), g When the viscosity is above a certain level, the outer layer of flexible glassy lithium-ion conductor changes from a rigid glassy state to a viscous flow state, and its viscosity is significantly reduced. It can undergo viscous flow between particles and at the interface, fully filling the micron-level gaps, and changing the solid-solid contact from point contact to surface contact, thereby greatly reducing the interfacial contact resistance. At the same time, this viscous flow characteristic helps the coating layer maintain a dense structure and no cracks during the cooling process, ensuring the long-term stability of the interface.
[0113] The second solution may include a glassy, flexible lithium-ion conductor and a second organic solvent.
[0114] The second organic solvent may include at least one of anhydrous ethanol, anhydrous acetonitrile, and dimethyl carbonate, and further, the second organic solvent may include anhydrous ethanol.
[0115] The second organic solvent meets the above-mentioned range and is able to dissolve or disperse the glassy flexible lithium-ion conductor in the second organic solvent to form a homogeneous and stable second solution (coating solution).
[0116] The concentration of the glassy flexible lithium-ion conductor in the second solution can be from 0.035 mol / L to 0.084 mol / L, for example, 0.035, 0.040, 0.050, 0.054, 0.060, 0.070, 0.080, 0.084 mol / L or any combination thereof.
[0117] The concentration of the glassy flexible lithium-ion conductor meets the above range, enabling the second coating material to form a continuous, uniform, and controllable thickness second coating layer on the particle surface of the intermediate.
[0118] The third stirring speed can be 300 rpm to 500 rpm, for example, 300, 400, 500 rpm or any combination thereof.
[0119] The third stirring speed meets the above range, which can form a uniform second mixture and promote uniform contact between intermediate particles and lithium-ion conductors with glassy flexibility.
[0120] The third stirring time can be 2 hours to 5 hours, for example, 2, 3, 4, 5 hours or any combination thereof.
[0121] The third stirring time meets the above range, which can form a uniform second mixture and promote uniform contact between intermediate particles and lithium-ion conductors with glassy flexibility.
[0122] The power of the second ultrasonic treatment is 100W to 200W, for example, 100, 150, 200 or any combination thereof.
[0123] The power of the second ultrasonic treatment meets the above range, which can break up agglomerates by means of cavitation effect and promote the second solution to enter the interparticle gaps more uniformly.
[0124] The second ultrasonic treatment time can be 10 min to 20 min, for example, 10, 15, 20 min or any combination thereof.
[0125] The second ultrasonic treatment time meets the above range, which can break up agglomerates by means of cavitation effect and promote the second solution to enter the interparticle gaps more uniformly.
[0126] The fourth stirring speed can be 300 rpm to 500 rpm, for example, 300, 400, 500 rpm or any combination thereof.
[0127] The fourth stirring speed meets the above range, which can keep the intermediate particles in a stable suspension state and promote the uniform adsorption or deposition of glassy flexible lithium-ion conductors on the particle surface.
[0128] The fourth stirring time can be 0.5h to 1h, for example, 0.5, 0.75, 1h or any combination thereof.
[0129] The fourth stirring time meets the above range, which can keep the intermediate particles in a stable suspension state and promote the uniform adsorption or deposition of glassy flexible lithium-ion conductors on the particle surface.
[0130] The second drying process may include a third and a fourth stage.
[0131] The temperature in the third stage can be 40℃ to 100℃, for example, 40, 50, 60, 70, 80, 90, 100℃ or any combination thereof.
[0132] The temperature in the third stage meets the above range, which can slowly remove the low-boiling-point second organic solvent and stabilize the surface deposit layer.
[0133] The third stage can last from 1 hour to 3 hours, for example, 1, 2, 3 hours or any combination thereof.
[0134] The third stage time meets the above range, which can slowly remove the low-boiling-point second organic solvent and stabilize the surface deposit layer.
[0135] The temperature of the fourth stage can be 100℃~120℃, for example, 100, 110, 120℃ or any combination thereof.
[0136] The temperature in the fourth stage meets the above range, which can further remove the residual second organic solvent and solidify the second coating precursor into a film.
[0137] The fourth stage can last from 3 to 5 hours, for example, 3, 4, 5 hours or any combination thereof.
[0138] The time of the fourth stage meets the above range, which can further remove the residual second organic solvent and solidify the second coating precursor into a film.
[0139] The temperature for the third annealing treatment can be 250℃~300℃, for example, 250, 260, 270, 280, 290, 300℃ or any combination thereof. Specifically, the heating rate for the third annealing treatment can be 2℃ / min.
[0140] The temperature of the third annealing process meets the above range, enabling the glassy flexible lithium-ion conductor to form a dense second coating layer on the outside of the intermediate particles, and maintaining a distinct composite coating structure with the aforementioned first coating layer.
[0141] The third annealing process can take 2 to 4 hours, for example, 2, 3, 4 hours or any combination thereof.
[0142] The time for the third annealing process meets the above-mentioned range, enabling the glassy flexible lithium-ion conductor to form a dense second coating layer on the outside of the intermediate particles, and maintaining a distinct composite coating structure with the aforementioned first coating layer.
[0143] This invention employs a stepwise coating and stepwise annealing process. Each coating layer independently undergoes wetting, gradient vacuum drying, and high-temperature annealing processes to ensure the complete formation of each layer structure and strong interfacial bonding. Compared to atomic layer deposition (ALD) and dry coating processes, this method eliminates the need for high-vacuum equipment and complex atmosphere control, significantly reducing equipment investment and operating costs. Simultaneously, the liquid phase system facilitates the uniform spreading of the coating precursor on the surface of the matrix particles, resulting in a more continuous, dense, and uniformly thick coating layer. The preparation method for this solid electrolyte is stable, simple to operate, and exhibits good reproducibility and batch consistency, making it easy to achieve large-scale mass production.
[0144] Thirdly, embodiments of the present invention provide a solid electrolyte membrane, comprising the above-described solid electrolyte or a solid electrolyte prepared according to the above-described solid electrolyte preparation method.
[0145] Solid electrolyte membranes possess excellent ion transport efficiency, interface stability, and machinability, which can effectively reduce the internal resistance of all-solid-state batteries, improve battery cycle life, rate performance, and safety, and have good prospects for industrial application.
[0146] Fourthly, embodiments of the present invention provide an electrode sheet, which may include an electrode current collector and an active coating present on at least one side of the current collector, wherein the active coating includes the above-mentioned solid electrolyte or a solid electrolyte prepared according to the above-mentioned solid electrolyte preparation method.
[0147] Specifically, the electrode may include at least one of a positive electrode and a negative electrode.
[0148] Solid electrolytes construct a continuous and efficient ion transport network in the electrode material layer, which significantly reduces the ion diffusion resistance inside the electrode, allowing the capacity of the active material to be fully released during the charging and discharging process.
[0149] Fifthly, embodiments of the present invention provide an all-solid-state battery, including the above-described solid electrolyte membrane or the above-described electrode sheet.
[0150] This all-solid-state battery, employing the aforementioned solid-state electrolyte, utilizes a sulfide solid-state electrolyte core to provide high lithium-ion conductivity. Local structural stability is adjusted through nitrogen-doped and / or fluorine-doped groups in the core lattice, thus balancing ion migration channels and intrinsic material stability. The first coating layer, acting as a chemically inert lithium-ion conductor, reduces side reactions caused by direct contact between the electrolyte and water, oxygen, or electrode materials. The second coating layer, acting as a glassy, flexible lithium-ion conductor, further improves the adhesion and fit between the particle surface and the electrode interface, resulting in more uniform interface contact and mitigating the increase in interface impedance. Therefore, the solid-state electrolyte forms a synergistic functional structure in the battery, with the doped matrix serving as the bulk ion conduction core and the double-layer coating layer acting as the surface chemical protection interface, significantly improving the cycle stability, rate performance, and safety of the all-solid-state battery.
[0151] The solid electrolyte of the present invention has good electrode compatibility and can be adapted to a variety of positive and negative electrode materials, thus having high practical application value.
[0152] The positive electrode material may include at least one of the following: high-nickel ternary positive electrode (NCM, NCA), lithium-rich manganese-based positive electrode, sulfide or sulfur-based positive electrode, and lithium cobalt oxide positive electrode; the negative electrode material may include at least one of the following: lithium metal, silicon-carbon or carbon-based negative electrode, graphite negative electrode, and Li-Al alloy negative electrode.
[0153] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0154] Example 1
[0155] This embodiment provides a method for preparing a solid electrolyte, the specific steps of which are as follows:
[0156] (1) Li2S (sulfide solid electrolyte precursor raw material), P2S5 (sulfide solid electrolyte precursor raw material), LiCl (sulfide solid electrolyte precursor raw material), LiBr (sulfide solid electrolyte precursor raw material), Li3N (doping source), Li3BO3 (glassy flexible lithium-ion conductor), and Li3PO4 (chemically inert lithium-ion conductor) were dried and dehydrated, and passed through a 200-mesh sieve. The raw material system including the sulfide solid electrolyte precursor raw material and the doping source was ground (ball-to-material ratio of 20:1) at a grinding speed of 400 rpm for 10 h. Then, a first annealing treatment was performed at 300℃ (heating rate of 2℃ / min) for 3 h. After natural cooling, the sulfide solid electrolyte precursor (Li3N-doped Li) was obtained. 5.5 PS 4.5 Cl 0.75 Br 0.75 Li3N and Li 5.5 PS 4.5 Cl 0.75 Br 0.75 The molar ratio is 0.01:1).
[0157] (2) 1g of sulfide solid electrolyte precursor and 10mL of a first solution containing Li3PO4 (containing a chemically inert lithium-ion conductor) (the concentration of Li3PO4 in the first solution is 0.020 mol / L, and the first solvent is anhydrous ethanol) were first mixed, and then stirred at 400rpm for 3h, intermittently sonicated at 150w for 10min (sonicated for 1min, stopped for 30s), and then stirred at 400rpm for 1h to obtain a first mixture (the solid content of the first mixture is 11%). Then the first mixture was subjected to a first drying treatment, wherein the temperature of the first stage was 60℃ and the time was 2h, the temperature of the second stage was 120℃ and the time was 4h, and then a second annealing treatment was performed at 280℃ (heating rate of 2℃ / min) for 2h to obtain an intermediate.
[0158] (3) The intermediate and 10 ml of the second solution of Li3BO3 (containing a glassy flexible lithium-ion conductor) were mixed for the second time (the concentration of Li3BO3 in the second solution was 0.045 mol / L, and the second solvent was anhydrous ethanol). The mixture was then stirred for the third time at 400 rpm for 3 h, intermittently sonicated at 150 W for 10 min (sonicated for 1 min, stopped for 30 s), and stirred for the fourth time at 400 rpm for 1 h to obtain the second mixture. The second mixture was then subjected to the second drying treatment, wherein the temperature of the third stage was 60 °C and the time was 2 h, the temperature of the fourth stage was 120 °C and the time was 4 h, and then the mixture was annealed for the third time at 280 °C (heating rate was 2 °C / min) for 2 h to obtain the solid electrolyte.
[0159] Example 2
[0160] This embodiment is basically the same as embodiment 1, except that in step (1), Li3N and Li 5.5 PS 4.5 Cl 0.75 Br 0.75 The molar ratio is 0.02:1, and the remaining steps are the same as in Example 1.
[0161] Example 3
[0162] This embodiment is basically the same as embodiment 1, except that in step (1), Li3N and Li 5.5 PS 4.5 Cl 0.75 Br 0.75 The molar ratio is 0.03:1, and the remaining steps are the same as in Example 1.
[0163] Example 4
[0164] This embodiment is basically the same as that of embodiment 1, except that: in step (2), the concentration of Li3PO4 in the first solution is 0.024mol / L; in step (3), the concentration of Li3BO3 in the second solution is 0.084mol / L, and the rest of the steps are the same as those of embodiment 1.
[0165] Example 5
[0166] This embodiment provides a method for preparing a solid electrolyte, the specific steps of which are as follows:
[0167] (1) Li2S (sulfide solid electrolyte precursor raw material), P2S5 (sulfide solid electrolyte precursor raw material), LiCl (sulfide solid electrolyte precursor raw material), LiBr (sulfide solid electrolyte precursor raw material), LiF (doping source), Li2B4O7 (glassy flexible lithium-ion conductor), and Li2CO3 (chemically inert lithium-ion conductor) were dried and dehydrated, and passed through a 200-mesh sieve. The raw material system including the sulfide solid electrolyte precursor raw material and the doping source was ground (ball-to-material ratio of 20:1) at a grinding speed of 300 rpm for 16 h. Then, a first annealing treatment was performed at 260℃ (heating rate of 2℃ / min) for 8 h. After natural cooling, the sulfide solid electrolyte precursor (Li doped with LiF) was obtained. 5.5 PS 4.5 Cl 0.75 Br 0.75 LiF and Li 5.5 PS 4.5 Cl 0.75 Br 0.75The molar ratio is 0.005:1).
[0168] (2) 1g of sulfide solid electrolyte precursor and 10mL of a first solution containing Li2CO3 (containing a chemically inert lithium-ion conductor) (the concentration of Li2CO3 in the first solution is 0.036 mol / L, and the first solvent is anhydrous ethanol) were first mixed, and then stirred at 300rpm for 5h, intermittently sonicated at 200W for 20min (sonication for 1min, stop for 30s), and then stirred at 300rpm for 0.5h to obtain a first mixture (the solid content of the first mixture is 11%). Then the first mixture was subjected to a first drying treatment, wherein the temperature of the first stage was 40℃ and the time was 3h, the temperature of the second stage was 110℃ and the time was 3h, and then a second annealing treatment was performed at 250℃ (heating rate of 2℃ / min) for 4h to obtain an intermediate.
[0169] (3) The intermediate and 10 ml of the second solution of Li2B4O7 (containing a glassy flexible lithium-ion conductor) were mixed for the second time (the concentration of Li2B4O7 in the second solution was 0.054 mol / L, and the second solvent was anhydrous ethanol). The mixture was then stirred for the third time at 300 rpm for 5 h, intermittently sonicated at 200 W for 20 min (sonication for 1 min, stop for 30 s), and stirred for the fourth time at 300 rpm for 0.5 h to obtain the second mixture. The second mixture was then subjected to the second drying treatment, wherein the temperature of the third stage was 40 °C and the time was 3 h, the temperature of the fourth stage was 110 °C and the time was 3 h, and then the mixture was annealed for the third time at 250 °C (heating rate of 2 °C / min) for 4 h to obtain the solid electrolyte.
[0170] Example 6
[0171] This embodiment provides a method for preparing a solid electrolyte, the specific steps of which are as follows:
[0172] (1) Li2S (sulfide solid electrolyte precursor raw material), P2S5 (sulfide solid electrolyte precursor raw material), LiCl (sulfide solid electrolyte precursor raw material), LiBr (sulfide solid electrolyte precursor raw material), LiF (doping source), LiBO2 (glassy flexible lithium-ion conductor), and Li2SO4 (chemically inert lithium-ion conductor) were dried and dehydrated, and passed through a 200-mesh sieve. The raw material system including the sulfide solid electrolyte precursor raw material and the doping source was ground (ball-to-material ratio of 20:1) at a grinding speed of 500 rpm for 8 h. Then, a first annealing treatment was performed at 320℃ (heating rate of 2℃ / min) for 6 h. After natural cooling, the sulfide solid electrolyte precursor (Li doped with LiF) was obtained. 5.5 PS4.5 Cl 0.75 Br 0.75 LiF and Li 5.5 PS 4.5 Cl 0.75 Br 0.75 The molar ratio is 0.01:1).
[0173] (2) 1g of sulfide solid electrolyte precursor and 10mL of a first solution containing Li2SO4 (containing a chemically inert lithium-ion conductor) (the concentration of Li2SO4 in the first solution is 0.036mol / L, and the first solvent is anhydrous ethanol) were first mixed, and then stirred at 500rpm for 2h, intermittently sonicated at 150W for 15min (sonicated for 1min, stopped for 30s), and then stirred at 500rpm for 0.75h to obtain a first mixture (the solid content of the first mixture is 15%). Then the first mixture was subjected to a first drying treatment, wherein the temperature of the first stage was 70℃ and the time was 1h, the temperature of the second stage was 100℃ and the time was 5h, and then a second annealing treatment was performed at 300℃ (heating rate of 2℃ / min) for 2h to obtain an intermediate.
[0174] (3) The intermediate and 10 ml of the second solution of LiBO2 (containing a glassy flexible lithium-ion conductor) were mixed for the second time. The mixture was stirred for the third time at 500 rpm for 2 h, intermittently sonicated at 150 W for 15 min (sonication for 1 min, stop for 30 s), and stirred for the fourth time at 500 rpm for 0.75 h to obtain the second mixture. The second mixture was then subjected to the second drying treatment, wherein the temperature of the third stage was 70 °C and the time was 1 h, the temperature of the fourth stage was 100 °C and the time was 5 h, and then the mixture was annealed for the third time at 300 °C (heating rate of 2 °C / min) for 2 h to obtain the solid electrolyte.
[0175] Example 7
[0176] This embodiment provides a method for preparing a solid electrolyte, the specific steps of which are as follows:
[0177] (1) Li2S (sulfide solid electrolyte precursor raw material), P2S5 (sulfide solid electrolyte precursor raw material), LiCl (sulfide solid electrolyte precursor raw material), LiBr (sulfide solid electrolyte precursor raw material), Li3N (doping source), Li3BO3 (glassy flexible lithium-ion conductor), and Li3PO4 (chemically inert lithium-ion conductor) were dried and dehydrated, and passed through a 200-mesh sieve. The raw material system including the sulfide solid electrolyte precursor raw material and the doping source was ground (ball-to-material ratio of 20:1) at a grinding speed of 400 rpm for 10 h. Then, a first annealing treatment was performed at 300℃ (heating rate of 2℃ / min) for 3 h. After natural cooling, the sulfide solid electrolyte precursor (Li3N-doped Li) was obtained. 5.5 PS 4.5 Cl 0.75 Br 0.75 Li3N and Li 5.5 PS 4.5 Cl 0.75 Br 0.75 The molar ratio is 0.01:1).
[0178] (2) 1g of sulfide solid electrolyte precursor and 10mL of a first solution containing Li3PO4 (containing a chemically inert lithium-ion conductor) (the concentration of Li3PO4 in the first solution is 0.015mol / L, and the first solvent is anhydrous ethanol) were first mixed, and then stirred at 300rpm for 2h, intermittently sonicated at 150w for 10min (sonicated for 1min, stopped for 30s), and then stirred at 300rpm for 0.5h to obtain a first mixture (the solid content of the first mixture is 8%). Then the first mixture was subjected to a first drying treatment, wherein the temperature of the first stage was 60℃ and the time was 2h, the temperature of the second stage was 120℃ and the time was 4h, and then a second annealing treatment was performed at 280℃ (heating rate of 2℃ / min) for 2h to obtain an intermediate.
[0179] (3) The intermediate and 10 ml of the second solution of Li3BO3 (containing a glassy flexible lithium-ion conductor) were mixed for the second time (the concentration of Li3BO3 in the second solution was 0.035 mol / L, and the second solvent was anhydrous ethanol). The mixture was then stirred for the third time at 300 rpm for 2 h, intermittently sonicated at 150 W for 10 min (sonicated for 1 min, stopped for 30 s), and stirred for the fourth time at 300 rpm for 0.5 h to obtain the second mixture. The second mixture was then subjected to the second drying treatment, wherein the temperature of the third stage was 60 °C and the time was 2 h, the temperature of the fourth stage was 120 °C and the time was 4 h, and then the mixture was annealed for the third time at 280 °C (heating rate was 2 °C / min) for 2 h to obtain the solid electrolyte.
[0180] Comparative Example 1
[0181] The process is basically the same as in Example 1, except that the sulfide solid electrolyte precursor is not coated, i.e. steps (2) and (3) are not performed. The remaining steps are the same as in Example 1.
[0182] Comparative Example 2
[0183] It is basically the same as Example 1, except that the first coating layer is Li3BO3 and the second coating layer is Li3PO4.
[0184] Specifically, in step (2), 1g of sulfide solid electrolyte precursor and 10mL of a second solution of Li3BO3 (containing a glassy flexible lithium-ion conductor) (the concentration of Li3BO3 in the second solution is 0.045mol / L, and the second solvent is anhydrous ethanol) are mixed for the second time. Then, the mixture is stirred for the third time at 400rpm for 3h, intermittently sonicated at 150w for 10min (sonicating for 1min, stopping for 30s), and stirred for the fourth time at 400rpm for 1h to obtain the second mixture. The second mixture is then subjected to a second drying treatment, wherein the temperature of the third stage is 60℃ and the time is 2h, the temperature of the fourth stage is 120℃ and the time is 4h, and then the mixture is annealed for the third time at 280℃ (heating rate is 2℃ / min) for 2h to obtain the intermediate.
[0185] In step (3), the intermediate and a first solution containing Li3PO4 (a chemically inert lithium-ion conductor) (the concentration of Li3PO4 in the first solution is 0.020 mol / L, and the first solvent is anhydrous ethanol) are first mixed, and then stirred at 400 rpm for 3 h, intermittently sonicated at 150 W for 10 min (sonication for 1 min, stop for 30 s), and then stirred at 400 rpm for 1 h to obtain the first mixture. Then the first mixture is subjected to a first drying treatment, wherein the temperature of the first stage is 60 °C and the time is 2 h, the temperature of the second stage is 120 °C and the time is 4 h, and then a second annealing treatment is performed at 280 °C (heating rate is 2 °C / min) for 2 h to obtain a solid electrolyte. The remaining steps are the same as in Example 1.
[0186] Comparative Example 3
[0187] The process is basically the same as in Example 1, except that: the first coating layer and the second coating layer are not distinguished, and Li3BO3 and Li3PO4 are prepared as a mixed solution and coated on the surface of the sulfide solid electrolyte precursor.
[0188] Specifically, 1g of sulfide solid electrolyte precursor and 10mL of a solution containing Li3PO4 (containing a chemically inert lithium-ion conductor) and Li3BO3 (containing a glassy flexible lithium-ion conductor) (the concentration of Li3PO4 in the solution is 0.020mol / L and the concentration of Li3BO3 is 0.045mol / L, with anhydrous ethanol as the solvent) were mixed. The mixture was then stirred at 400rpm for 3h, intermittently sonicated at 150w for 10min (sonication for 1min, pause for 30s), and stirred at 400rpm for 1h to obtain a mixture. The mixture was then dried, with the first stage at 60℃ for 2h and the second stage at 120℃ for 4h. Subsequently, a second annealing treatment was performed at 280℃ (heating rate of 2℃ / min) for 2h to obtain a solid electrolyte. The remaining steps were the same as in Example 1.
[0189] Test case
[0190] 1. Calculation of the molar ratio of the coating layer
[0191] The molar ratio of the first coating layer to the second coating layer (the molar ratio of the inner and outer coating layers) is calculated using Equation 1:
[0192] Formula 1,
[0193] In Equation 1, V 内 The volume of the solution containing the first coating layer material (inner coating material) is expressed in liters (L); C 内 V represents the concentration of the solution containing the first coating layer material (inner coating material), in mol / L. 外 The volume of the solution containing the second coating layer material (outer coating layer material) is expressed in L; C 外 The concentration of the solution containing the second coating material (outer coating material) is expressed in mol / L.
[0194] The molar ratio of the first coating layer to the second coating layer of the solid electrolyte (the molar ratio of the inner and outer coating layers) is shown in Table 1.
[0195] 2. Coating thickness test
[0196] The thicknesses of the first and second coating layers were determined by transmission electron microscopy (TEM).
[0197] The thicknesses of the first and second coating layers of the solid electrolyte are shown in Table 1.
[0198] Table 1
[0199]
[0200] 3. Solid electrolyte performance testing
[0201] (1) Sample preparation
[0202] The solid electrolytes prepared in the examples and comparative examples were ground in a mortar and pestle, and the resulting powder was passed through a 300-mesh standard sieve. The powder passing through the sieve was collected for later use. Under an inert atmosphere (argon atmosphere, water and oxygen content both <0.1ppm), the sieved electrolyte powder was pressed into shape at room temperature (25°C) with a uniaxial pressure of 380MPa to obtain solid electrolyte sheets with a diameter of approximately 1cm and a thickness of 0.7mm~0.9mm.
[0203] (2) Ionic conductivity test
[0204] The ionic conductivity of the solid electrolyte sheet was tested using the electrochemical impedance spectroscopy (EIS). The electrolyte sheet was placed between two blocking electrodes (stainless steel or gold electrodes), and an AC signal with an amplitude of 10 mV and a frequency range of 1 Hz to 1 MHz was applied under constant temperature conditions of 25 °C. The sum of the bulk resistance and grain boundary resistance (total resistance R) of the solid electrolyte sheet was obtained by fitting the AC impedance spectrum using an equivalent circuit, and the ionic conductivity was calculated according to Equation 2.
[0205] Equation 2,
[0206] In Equation 2, σ is the ionic conductivity, in S / cm; L is the thickness of the solid electrolyte sheet, in cm; S is the effective area of the solid electrolyte sheet, in cm²; and R is the total resistance, in Ω. Each group of samples was tested in parallel three times, and the average value was taken.
[0207] (3) Air stability test
[0208] The solid electrolyte powders prepared in the examples and comparative examples were uniformly spread in a glass petri dish and exposed to air at room temperature (25°C) and relative humidity of 20%~30% for 24 hours. After exposure, the powders were pressed into solid electrolyte sheets again according to the sample preparation method described above, and their ionic conductivity was tested under the same conditions.
[0209] (4) Calculation of ionic conductivity retention rate
[0210] The retention rate of ionic conductivity is calculated according to Equation 3:
[0211] Formula 3,
[0212] In Equation 3, σinitial represents the room-temperature ionic conductivity of the solid electrolyte sheet before air exposure, in units of S / cm, and σexposed represents the room-temperature ionic conductivity of the solid electrolyte sheet after 24 hours of air exposure, also in units of S / cm. A higher retention rate indicates better air stability of the solid electrolyte.
[0213] The test and calculation results of room temperature ionic conductivity, air exposure ionic conductivity for 24 hours, and ionic conductivity retention rate are shown in Table 2.
[0214] Table 2
[0215]
[0216] Conclusion Analysis:
[0217] This invention utilizes a synergistic design of bulk doping and gradient coating to prepare a solid-state electrolyte that combines high ionic conductivity with excellent air stability. Bulk doping optimizes the matrix lattice structure, ensuring efficient lithium-ion transport; the double-layer coating achieves hierarchical control of the interfacial chemical environment through functional partitioning—the inner layer focuses on chemical protection, while the outer layer focuses on ion conduction and interfacial adaptation. This synergistic strategy effectively overcomes the technical challenge of achieving multiple performance characteristics simultaneously through single modification methods, and the resulting solid-state electrolyte shows promising potential for all-solid-state battery applications.
[0218] 4. Performance testing of all-solid-state batteries
[0219] The solid electrolyte materials prepared in the above embodiments and comparative examples were used to assemble all-solid-state batteries. The specific steps are as follows:
[0220] Ternary cathode material (NCM), solid electrolyte material, conductive agent (vapor-grown carbon fiber, VGCF), and binder (polytetrafluoroethylene, PTFE) were weighed and mixed uniformly at a mass ratio of 60:25:2:0.5, and then rolled to form a cathode film. The cathode film was then composited with a stainless steel current collector to obtain a cathode electrode sheet. Solid electrolyte material and binder (PTFE) were mixed uniformly at a mass ratio of 100:0.5 and rolled to form an electrolyte film. Using lithium metal sheets as the anode, under an inert atmosphere (argon atmosphere, water and oxygen content both <0.1ppm), the cathode electrode sheet, electrolyte film, and anode sheet were stacked sequentially to assemble an all-solid-state battery.
[0221] The electrochemical performance of the assembled all-solid-state battery was tested using the following methods:
[0222] (1) Rate performance test: Constant current charging was performed at a rate of 0.1C, and then constant current discharge was performed at rates of 0.1C and 1C respectively. The discharge capacity at each rate was recorded. The rate retention rate was calculated according to the following formula: Rate retention rate (%) = (1C discharge capacity / 0.1C discharge capacity) × 100%.
[0223] (2) Initial coulombic efficiency test: Constant current charge and discharge test was performed at a rate of 0.1C, and the initial charge capacity and initial discharge capacity were recorded. The initial discharge specific capacity is the discharge specific capacity of the material at 0.1C (mAh / g), and the initial coulombic efficiency is calculated by the following formula: Initial coulombic efficiency (%) = (initial discharge capacity / initial charge capacity) × 100%.
[0224] All the above tests were conducted at room temperature (25°C), and the test results of each embodiment and comparative example are shown in Table 3.
[0225] Table 3
[0226]
[0227] Conclusion Analysis:
[0228] In summary, this invention effectively improves the overall performance of solid-state electrolytes through a synergistic modification strategy of lithium nitride bulk doping and gradient coating. On the one hand, the gradient coating layer can construct a continuous ion conduction network on the surface of the positive electrode active material, significantly reducing the solid-solid interface contact impedance between the electrolyte and active particles. On the other hand, the combined effect of bulk doping and dense coating layer enhances the structural stability and resistance to environmental degradation of the material, enabling the solid-state electrolyte to possess both good air stability and high ionic conductivity. When applied to solid-state batteries, it can effectively improve the cycle performance and rate performance of the battery, exhibiting excellent electrochemical performance.
[0229] The solid electrolyte of this invention has good electrode compatibility and can be adapted to a variety of positive and negative electrode materials. It can significantly improve the cycle stability, rate performance and safety of all-solid-state batteries and has high practical application value.
[0230] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid electrolyte, characterized in that, The device includes a core, a first coating layer located on at least a portion of the surface of the core, and a second coating layer located on at least a portion of the surface of the first coating layer opposite to the core; wherein the core includes a sulfide solid electrolyte, the sulfide solid electrolyte including dopant groups doped in a crystal lattice, the dopant groups including nitrogen dopant groups and / or fluorine dopant groups; the first coating layer includes a chemically inert lithium-ion conductor; and the second coating layer includes a glassy flexible lithium-ion conductor.
2. The solid electrolyte according to claim 1, characterized in that, The matrix of the sulfide solid electrolyte includes Li 5.5 PS 4.5 Cl 1.5-x Br x , 0≤x≤1.
5.
3. The solid electrolyte according to claim 1 or 2, characterized in that, The chemically inert lithium-ion conductor includes at least one of lithium phosphate, lithium carbonate, and lithium sulfate; And / or, the glassy flexible lithium-ion conductor includes at least one of lithium borate, lithium metaborate, and lithium tetraborate.
4. The solid electrolyte according to claim 1 or 2, characterized in that, The molar ratio of the chemically inert lithium-ion conductor to the glassy flexible lithium-ion conductor is (2~4):(6~8). And / or, the thickness of the first coating layer is 5nm~15nm; And / or, the thickness of the second coating layer is 5nm~25nm; And / or, the ratio of the mass of the core to the sum of the masses of the first coating layer and the second coating layer is 1:(0.01~0.05).
5. A method for preparing a solid electrolyte according to any one of claims 1-4, characterized in that the step... include: (1) A raw material system including sulfide solid electrolyte precursor raw material and doping source is subjected to grinding and first annealing treatment in sequence to obtain sulfide solid electrolyte precursor; wherein, the doping source includes nitrogen doping group and / or fluorine doping group. (2) The sulfide solid electrolyte precursor and the first solution containing the chemically inert lithium-ion conductor are first mixed to obtain a first mixture; then the first mixture is subjected to a first drying treatment and a second annealing treatment to obtain an intermediate. (3) The intermediate and the second solution containing the glassy flexible lithium-ion conductor are mixed for the second time to obtain the second mixture; then the second mixture is subjected to a second drying treatment and a third annealing treatment in sequence to obtain the solid electrolyte.
6. The method for preparing a solid electrolyte according to claim 5, characterized in that, The doping source includes at least one of lithium nitride and lithium fluoride; And / or, the sulfide solid electrolyte precursor raw material includes at least one of Li2S, P2S5, LiCl, and LiBr; And / or, the molar ratio of the doping source to the matrix of the sulfide solid electrolyte is (0.005~0.04):
1.
7. The method for preparing a solid electrolyte according to claim 5 or 6, characterized in that, The grinding speed is 300 rpm to 500 rpm; And / or, the grinding process takes 8 to 16 hours; And / or, the temperature of the first annealing treatment is 260℃~320℃; And / or, the first annealing process takes 5 to 10 hours.
8. The method for preparing a solid electrolyte according to claim 5 or 6, characterized in that, The first solution further includes a first organic solvent, which includes at least one of anhydrous ethanol, anhydrous acetonitrile, and dimethyl carbonate; And / or, the concentration of the chemically inert lithium-ion conductor in the first solution is 0.015 mol / L to 0.036 mol / L; And / or, the second solution further includes a second organic solvent, the second organic solvent including at least one of anhydrous ethanol, anhydrous acetonitrile, and dimethyl carbonate; And / or, the concentration of the glassy flexible lithium-ion conductor in the second solution is 0.035 mol / L to 0.084 mol / L.
9. The method for preparing a solid electrolyte according to claim 5 or 6, characterized in that, The solid content of the first mixture is 8% to 15%; And / or, the process of first mixing the sulfide solid electrolyte precursor and the first solution containing the chemically inert lithium-ion conductor to obtain the first mixture includes: The sulfide solid electrolyte precursor and a first solution containing the chemically inert lithium-ion conductor are mixed, and then subjected to a first stirring, a first ultrasonic treatment, and a second stirring in sequence to obtain the first mixture. The first stirring is performed at a speed of 300 rpm to 500 rpm for 2 h to 5 h, the first ultrasonic treatment is performed at a power of 100 W to 200 W for 10 min to 20 min, and the second stirring is performed at a speed of 300 rpm to 500 rpm for 0.5 h to 1 h. And / or, the first drying process includes a first stage and a second stage, wherein the temperature of the first stage is 40℃~100℃ and the time is 1h~3h, and the temperature of the second stage is 100℃~120℃ and the time is 3h~5h; And / or, the temperature of the second annealing treatment is 250℃~300℃; And / or, the second annealing process takes 2 to 4 hours.
10. The method for preparing a solid electrolyte according to claim 5 or 6, characterized in that, The process of mixing the intermediate with the second solution containing the glassy, flexible lithium-ion conductor to obtain the second mixture includes: The intermediate and the second solution containing the glassy flexible lithium-ion conductor are mixed, and then subjected to third stirring, second ultrasonic treatment, and fourth stirring to obtain the second mixture. The third stirring speed is 300 rpm to 500 rpm and the time is 2 h to 5 h. The power of the second ultrasonic treatment is 100 W to 200 W and the time is 10 min to 20 min. The fourth stirring speed is 300 rpm to 500 rpm and the time is 0.5 h to 1 h. And / or, the second drying process includes a third stage and a fourth stage, wherein the temperature of the third stage is 40℃~100℃ and the time is 1h~3h, and the temperature of the fourth stage is 100℃~120℃ and the time is 3h~5h; And / or, the temperature of the third annealing treatment is 250℃~300℃; And / or, the third annealing process takes 2 to 4 hours.
11. A solid electrolyte membrane, characterized in that, This includes the solid electrolyte as described in any one of claims 1-4 or the solid electrolyte prepared by the method described in any one of claims 5-10.
12. An electrode sheet, characterized in that, The electrode includes a current collector and an active coating present on at least one side of the current collector, wherein the active coating includes the solid electrolyte according to any one of claims 1-4 or the solid electrolyte prepared by the method according to any one of claims 5-10.
13. The electrode sheet according to claim 12, characterized in that, The electrode is either a negative electrode or a positive electrode.
14. An all-solid-state battery, characterized in that, Includes the solid electrolyte membrane of claim 11 or the electrode of claim 12 or 13.
